2019
DOI: 10.1111/pai.13019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food allergy on food insecurity and health literacy in a tertiary care pediatric allergy population

Abstract: Background Food insecurity (FI), limited availability of or access to nutritional foods, is linked to poor child/caregiver health. We examined FI in food‐allergic and non‐food‐allergic children to determine whether dietary limitations associated with food allergy increases risk of FI. Methods Food‐allergic and non‐food‐allergic children (1‐17 years) were recruited from Arkansas Children's Hospital allergy/asthma clinics. The USDA Food Security Survey, the Newest Vital Sign Health Literacy (HL) questionnaire, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…However, out-of-pocket expenses were found to account for a sizeable proportion of the additional costs of food allergy as well. Not surprisingly, research suggests lower income families are disproportionately affected by the costs of pediatric food allergy [11][12][13], including the costs of epinephrine auto-injectors (EAIs) [11]. However, the economic impact of pediatric food allergy on lower income families is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, out-of-pocket expenses were found to account for a sizeable proportion of the additional costs of food allergy as well. Not surprisingly, research suggests lower income families are disproportionately affected by the costs of pediatric food allergy [11][12][13], including the costs of epinephrine auto-injectors (EAIs) [11]. However, the economic impact of pediatric food allergy on lower income families is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…13 Allergen avoidance imposes dietary restrictions, with potential nutritional consequences, and can lead to food insecurity. [14][15][16] Eighty-six per cent of mothers of children with suspected FA avoid foods on their own initiative. 17 Goldberg et al 16 have recently shown that milk-allergic young adults have reduced bone mineral density and that low calcium intake, asthma and weight constitute independent risk factors.…”
mentioning
confidence: 99%
“…We also did not collect data on the type or number of household food allergies, which might modulate food accessibility or financial burden of the restriction. 60 …”
Section: Discussionmentioning
confidence: 99%